Proposed Marketing Strategy in Terms of Changes in Channel and Pricing Strategy of Foglia with The Purpose to Imporve The Sales (The Indonesian Journal of Business Administration, 2013)
The fashion industry is as old as the idea of wearing clothes. This industry was born and evolved along with the increasing need for clothing. The increasing need for clothes opened many opportunities for businessmen offer many varied designs of clothes for the customer. Foglia is a new player in the fashion business. The company is established in July 2011. Foglia is a company engaged in woman’s clothing boutique online concept. Foglia creates its own design with a touch of lace as a uniqueness for every clothes offered. During the business, Foglia faces several issues. The most prominent issues are about pricing, promotion, and company business. Internal and external analysis are done to find the root cause. Internal analysis is performed to determine the strength and the weakness of the company whereas external analysis is performed to find out the external factor of the business that can influence the company. According to the analysis, there are two root causes. They are 1) Gap of pricing (company’s price tends to be expensive than customer willing to pay), and 2) Company business (remain on an online store boutique concept or do both online and offline store). Problem solving on this study begins with determining the company business, it is done based on the behavioral about buying clothes of the intended target market. The choices are remaining on online store boutique concept, changing in offline store boutique concept, or doing both online and offline boutique concept. The final step is determining the pricing strategy for Foglia in order to conform with the intended target market. The propose solution for Foglia is do online and offline boutique concept. This is done to attract prospective customers who usually buy clothes in online store and physical stores. The last solution is set the appropriate price by using penetration pricing strategy and choosing promotion price strategy to stimulate early purchase from the customer and to expand the market share of Foglia. Keywords: Online Store, Offline Store, Penetration Price, Promotion Price, and Fashion